Ironia verbal: do conceito Skinneriano á análise do discurso jurídico irônico - Messa, Luciana Chequer Saraiva (2011)
This paper presents two studies of verbal irony in Behavior Analysis. This work shows the contributions of other areas (Linguistics, Cognitive Psychology) for Behavior Analysis, so that it can construct in behavioral foundations, a sustainable framework for studying the functions of production and comprehension of verbal irony, and, at the same time, so they can test empirically some of the verbal irony interpretations. The first study is conceptual and is intended to introduce the concept of irony in two areas of knowledge :Linguistics, through the author Paiva (1961), A Contribution to The Stylistics Irony, and Behavior Analysis, through the author Skinner (1957), Verbal Behavior. From these two classics, was analyzed and discussed through the method of BAS (Behavioral Analysis of Speech), the concept of verbal irony and the possibilities for a functional analysis of verbal behavior that involves the phenomenon. This method is self-description of the effects of text-speech under the researcher. The results showed that the irony in Skinner can be conceptualized as verbal behavior under multiple control - multiple audience, multiple stimuli (especially non-verbal) and motivational operations from these stimulus and multiple audiences - with the function of allowing the listener to produce a response (in general, contrary to what was said). The different consequences on audiences, functionally classify subtypes of irony (sarcasm, satire, allegory, cynicism, etc).The authors Skinner and Paiva share the same elements of irony concept. Skinner describes the function of irony from the context of multiple control on verbal behavior (ironic), that includes more than one audience as part of that context; Paiva demonstrates an outstanding contribution in the differentiation of five types (pure, satirical, disfemistic, restrictive and contornant) and climates (naive, rhetoric, sacred, scientific and familiar) of irony. The junction of the approaches of Skinner and Paiva suggests that investigation of irony in speech should analyze the production and comprehension of verbal irony considering the context (stimulus control) and the audience that define multiple types of climates and ironies. We conclude that functional analysis of verbal irony helped to go beyond simply saying how irony it is "used", indicating where, how and why (for what) this behavior is emitted. Study II presents an empirical analysis of production and comprehension of verbal irony in the legal environment. A Jury was recorded, filmed and the speech of the Prosecutor and Lawer was analysed. From the recorded statements, four ironic phrases were selected from each participant, chosen by the researcher and judged by three people (a trainee, the supervisor of this dissertation and the participant s opponent). The phrases were separated and analyzed using the BAS method. The results demonstrated a clear understanding of the participant s irony by definition in the dictionary. Moreover, the high emission of manipulative autoclitics made the irony be issued more in order to persuade listeners than to humor function, for example. It was concluded that the emission of irony can be understood as something inappropriate in legal environment. Furthermore, when investigated by the Behavior Analysis (along with the addition of Linguists definitions), is issued under multiple control, highlighting the humor functions and disqualification of the opponent s speech (such as sarcasm or mockery).